Comparison of Color Change of Silorane and Methacrylate-Based Composites Due to Bleaching - Sedigheh Hashemi Kamangar; Kiyana Kiakojoori; Mansoreh Mirzaii; Mohammadjavad Kharazifard (Islamic Dental Association of Iran, 2015)
Background and Aim: Bleaching agents differently affect the color of composite restorations. This study aimed to assess the effect of two different bleaching agents on color change of silorane-based and two types of methacrylate-based composites. Materials and Methods: This in-vitro study was conducted on 18 disc-shaped specimens measuring 10×2mm made of A3 shade of Z250, Z350 and P90 composites. The speci-mens were randomly divided into three groups (n=6). Group one or control samples were stored in distilled water. Groups two and three were subjected to bleaching with 16% and 35% carbamide peroxide (CP) (Kimia, Chemident, Iran). Color parameters of specimens were measured before and after bleaching using the CIE L*a*b* system and a spectrophotometer. Data were analyzed using repeated measures ANOVA and Tukey's HSD test for multiple comparisons. Results: The mean and standard deviation (SD) of total color change (&DeltaE) of Z250 in dis-tilled water, 16% carbamide peroxide and 35% carbamide peroxide was 3.48±1.43, 4.55±1.7 and 4.17±1.9, respectively. These values were 4.33±2.41, 4.94±2.23 and 4.25±1.65 for Z350 and 4.97±2.47, 5.28±1.67 and 3.41±2.26 for P90, respectively. Conclusion: In general, the color change of microhybrid, nanofilled and silorane-based composites following bleaching with different bleaching agents was clinically perceivable.